Drug utilization and potentially inappropriate drug use in elderly residents of a community in Istanbul, Turkey - AKICI, AHMET; AY, NADİYE PINAR (Dustri-Verlag Dr. Karl Feistle, 2005)
Objective: This study investigates drug utilization and estimates the prevalence of potentially inappropriate drug use in a Turkish population aged 70 years or older. Material and methods: A cross-sectional study was carried out on a total of 1,019 participants who accepted face-to-face questionnaires in home interviews in Istanbul. All medications used in the three weeks prior to the study were recorded. Some major risk factors that might influence the use of inappropriate medication such as socio-demographic characteristics and concomitant disease such as depression and dementia were also questioned. Inappropriate drug use was assessed using the Beers criteria. Results: Among the 1,019 participants, 903 (88.6%) had been using at least one medication during the last three weeks. The average number of medications used was 2.9 ± 2.0. The most frequently drugs used were cardiovascular drugs (39.9%), followed by analgesics /anti-inflammatory drugs (16.2%), vitamin/mineral preparations (10.6%) and central nervous system drugs (10.2%). Of the 1,019 participants, 9.8% were using one potentially inappropriate medication and one patient was using two inappropriate drugs. The most common of these drugs were reserpine (23.7%), dipyridamole (21.8%), antihistamines (14.8%), and benzodiazepines (10.9%). Only age and total number of medications were associated with potentially inappropriate drugs in the multivariate analysis. Conclusions: This study revealed that drug utilization and the prevalence of inappropriate medication use in the elderly were lower than in published reports from most developed countries. Furthermore, polypharmacy and higher age were the main risk factors for potentially inappropriate drug use in the elderly. ©2005 Dustri-Verlag Dr. K. Feistle.
Keywords: Beers criteria; Drug utilization; Elderly; Inappropriate medication; Prescription